LEARNING MOTIVATION AND ENGLISH ACHIEVEMENT OF STUDENTS AT POLITEKNIK NEGERI SEMARANG CENTRAL JAVA - Fadillah, Ridha (Universitas Muhammadiyah Surakarta, 2014)
The aim of this study was to investigate the correlation between learning motivation and English achievement of students of Mechanical Engineering at Politeknik Negeri Semarang, Central Java. The subjects of this study were 147 students aged seventeen to twenty one years old. The data were collected using questionnaire and analyzed using the Statistic Package for Social Science. The result indicate that the studentsâ motiva- tion in learning English was at moderate level. They were most motivated in learning situation, intrinsic interest, going abroad, immediate achievement, social responsibility, individual development, and the students were least motivated in information medium. There was no significant relationship between studentsâ learning motivation types and their English achievements as a whole. However, there is no significant positive correlations among immediate achievement, learning situation and studentsâ outcomes were indicated. In general, Politeknik Negeri Semarang students had low motivation in their English course but they still had good achievements. It was seen from the negative correlation between the two variables. In other words, the learning motivation does not influence their achievements.Â